PROIECTAREA CROSS-CURRICULUMULUI EDUCAŢIEI INTERCULTURALE - USM ADMIN (Moldova State University, 2010)
Cross - curriculum is one of the most frequently used modality of teaching. It is beyond the excessive academic rigidity and orientation of the traditional subjects/courses exploring the complex world and interaction we live in. This approach of the curriculum through introduction/integration of the cross-curricular themes assumes: - possibility to get out of the subject "box" for both teachers and pupils/students; - opening towards the real world, towards the life the way it is lived by those who learn; - promoting a constructive vision on teaching in which the pupil/student has a fundamental role by an active participation in the projection and expression of their own experience of learning; - capitalization of a wide spectrum of themes/problems being most frequently taken from the social life, thus ren- dering competences and values to students who need these values to apply them successfully in their personal, professional and social life.